2016
DOI: 10.1134/s0742046316040047
|View full text |Cite
|
Sign up to set email alerts
|

A geomechanical interpretation of the local seismicity related to eruptions and renewed activity on Tolbachik, Koryakskii, and Avacha Volcanoes, Kamchatka, in 2008–2012

Abstract: The local seismicity during the 2012-2013 eruption of Tolbachik Volcano and the 2008-2009 steam-gas eruption of Koryakskii Volcano is here considered as resulting from injections of magma that produced dikes, sills, and renewed activity at preexisting faults. We identified plane-oriented earthquake clusters in order to reveal the above zones using earthquake catalogs made at the Kamchatka Branch of the Geophysical Service of the Russian Academy of Sciences (KB GS RAS). Subsequent space-time analysis of these o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…A.V. Kiryukhin et al (2015Kiryukhin et al ( , 2016 proposed a method for identifying and estimating the geometry of magmatic plumbing systems of volcanoes (dikes and sills) based on local seismicity data. This method was described in detail for the 2012-2013 eruption of Tolbachik Volcano with more data on the 2008-2010 activation of the Koryakskii-Avacha Volcanic Cluster.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A.V. Kiryukhin et al (2015Kiryukhin et al ( , 2016 proposed a method for identifying and estimating the geometry of magmatic plumbing systems of volcanoes (dikes and sills) based on local seismicity data. This method was described in detail for the 2012-2013 eruption of Tolbachik Volcano with more data on the 2008-2010 activation of the Koryakskii-Avacha Volcanic Cluster.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper furnishes a more detailed and complete (supplemented with observations in 2014-2016) description of the magmatic plumbing system beneath the Koryakskii-Avacha Volcanic Cluster, estimates the geomechanical conditions at the basement of this cluster, simulates magma emplacement into a fissure zone that is typical of the current conditions, and quotes factual data on the thermal action of a dike on the discharge of a nearby thermal spring. The raw data, as well as the method and criteria for identification of plane-oriented earthquake clusters as observed during the 2008-2010 active period of Koryakskii and Avacha volcanoes were described by Kiryukhin et al (2016). For the present study the catalog of seismic data (January 200 to January 2013) was used along with published data (Zemletryaseniya …, 2015(Zemletryaseniya …, , 2016 and with data from the Preliminary Catalog compiled at the Kamchatka Branch, Geophysical Survey, Russian Academy of Sciences (KB GS RAS) for 2015-2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of 3D geomechanical modeling indicated that the deformation observed during the time span of interest (1 year) was the result of the emplacement of a radial dike into Tolbachik Volcano (with a dip angle of 80 ∘ to the westnorthwest). Later, a more detailed analysis of seismic data preceding the November 27, 2012, Tolbachik lava eruption [5] revealed that the injection of magma resulted in a series of dikes trending west-northwestward at absolute depths ranging from −4 to +3 km in a zone situated to the southeast of the Ploskii Tolbachik Volcano edifice. The dikes penetrated into a nearly horizontal permeable zone at an absolute depth of approximately zero, producing sills and emplacing a magma-conducting dike along the top of the zone of cinder cones (with a dip angle of 50 ∘ toward the azimuth at 300 ∘ ), which was located 5.5 km from the epicenter of the initial magma injection.…”
Section: Brief Review Of Studies Of Magma Plumbing Systems Of Volcanoesmentioning
confidence: 99%
“…Thus, in this paper, we used plane-oriented earthquake clusters (retrieved from the Kamchatka Branch of the Geophysical Survey Russia Academy of Sciences (KB GS RAS) catalogs [2001][2002][2003][2004][2005][2006][2007][2008][2009][2010][2011][2012][2013][2014][2015][2016] to track dikes injected below the above-mentioned volcanoes [5,6]. The magma injection zones (i.e., dikes and chamberlike shapes) defined using this method were defined as heat sources for their adjacent hydrogeological reservoirs and surface features (hot springs and fumaroles) in terms of thermal-hydrodynamic models.…”
Section: Introductionmentioning
confidence: 99%